2011
DOI: 10.1002/bit.24357
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c dissolved in 1‐allyl‐3‐methylimidazolium chloride type ionic liquid undergoes a quasi‐reversible redox reaction up to 140°C

Abstract: Solubility of cytochrome c, a typical heme protein, in a various ionic liquids has been analyzed. The solubility has been discussed with polarity parameters of the ionic liquids. Both hydrogen bond basicity and dipolarity/polarizability of the ionic liquids were confirmed to be influential factors to control the solubilization of cytochrome c. Polar ionic liquids such as 1-butyl-3-methylimidazolium chloride and 1-allyl-3-methylimidazolium chloride solubilized cytochrome c at 80°C, and the dissolved cytochrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 50 publications
(53 reference statements)
2
40
0
Order By: Relevance
“…This occurs even though the ILs have a different affinity owing to the anionic structures. Despite the fact that [BMI]Cl has a high β value and [BMI] [Tf 2 N] has a low β value [28], both ILs form a cholesterol-water interface. These observations suggest that [EMI][Lac] and [Ch][Lac] will also localize around the lipid-water interface in a vesicle solution.…”
Section: Discussionmentioning
confidence: 99%
“…This occurs even though the ILs have a different affinity owing to the anionic structures. Despite the fact that [BMI]Cl has a high β value and [BMI] [Tf 2 N] has a low β value [28], both ILs form a cholesterol-water interface. These observations suggest that [EMI][Lac] and [Ch][Lac] will also localize around the lipid-water interface in a vesicle solution.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Furthermore, as the first research group, which converted the chemical oscillation of a BZ reaction into a mechanical change in polymer gels, we have been systematically studying a "self-oscillating gel" that exhibits an autonomous swelling-deswelling oscillation under nonoscillatory outer conditions. [15] Ohno and coworkers also found that cytochrome c retained 70 % of its original activity for a long period of time (as long as 18 months) in a mixture of choline dihydrogen phosphate PIL and water, [16] known as a "hydrated IL". [10][11][12] These properties are a high ion conductivity, non-flammability, (electro)chemical stability, and thermal stability.…”
mentioning
confidence: 99%
“…[13] ILs can be divided generally into two categories: ILs with an ion structure that includes active protons (protic ILs: PILs) and that does not include active protons (aprotic ILs: APILs). [15] Ohno and coworkers also found that cytochrome c retained 70 % of its original activity for a long period of time (as long as 18 months) in a mixture of choline dihydrogen phosphate PIL and water, [16] known as a "hydrated IL". PILs are assumed to be a promising class of a preservation medium for biopolymers.…”
mentioning
confidence: 99%
“…Polar ILs exhibit extremely high hydrogen bond basicity 14 and are reported to be good solvents for some poorly soluble materials such as polysaccharides and proteins. 13,57 The second-generation polar ILs, namely phosphonate-and carboxylate-type ILs, have recently gained special importance owing to their high polarity and low viscosity as compared to those of chloride-type ILs. 2,3,8 Since cellulose displays high crystallinity and poor solubility, many studies have reported enzymatic hydrolysis of cellulose after pretreatment with polar ILs.…”
mentioning
confidence: 99%
“…11,12 While reports show that only chloride-type ILs can dissolve cytochrome c (cyt c) without denaturation, 13 phosphonate-type ILs cause its denaturation. On the other hand, Fujita et al reported that certain ILs, typically composed of choline dihydrogen phosphate and a small volume of water, enhance protein stabilization without denaturation in the presence of a small volume of water.…”
mentioning
confidence: 99%